Networked Publics and the Social Construction of Death, Dying and Bereavement in a Digital Age - Kiel, Paula (AoIR Selected Papers of Internet Research, 2017)
For the past two decades, as in so many other fields of our social lives, digital media has permeated the field of death, dying and bereavement. Death-related online practices keep emerging, offering a range of ways of dealing with death digitally. Online memorials, online support groups and grief-specific forums, expression of grief on Facebook, funerals on virtual worlds, digital legacy services and post-mortem online communication are but a few examples of the variety of such death-related online practices. To a great extent many of these practices are arguably transforming the contemporary social construction of death, mainly by making death public and creating death-specific networked publics. While many scholars in the field of digital death and thanatology are fascinated with these processes, additional critical engagement with the limitations, challenges and exclusions implicated by these practices is required. By focusing on the specific practice of post-mortem online communication, this paper highlights some of these main challenges, linking them critically to some of the fundamental issues of networked publics in an increasingly digitised media world.